Physicochemical Characteristics of Jelly Candy Cinnamon Powder Koerintji Variation of Red Seaweed Carrageenan Concentration - Setiawan, Erwin; Ujianti, Rizky Muliani Dwi; Muflihati, Iffah; Affandi, Arief Rakhman (Biology, Medicine, & Natural Product Chemistry, 2024)
Jelly candy is a product that has the characteristics of being chewy and varied in texture. Carrageenan, an alternative natural raw material as a gelling agent in jelly candy, is one of the producers of red seaweed carrageenan because it has a very complex composition. Cinnamon contains about 91.88-94.19% cinnamaldehyde as an antioxidant compound. The study aimed to determine the value of the antioxidant activity obtained and the correlation between the cinnamon powder jelly candy Koerintji variety and the addition of red seaweed carrageenan with different concentration variations. The study was conducted using a completely randomized design with two factors. Carrageenan concentrations consist of 3.5% and 5%. The results showed that the concentration of red seaweed carrageenan significantly affected the antioxidant activity value and characteristics of cinnamon jelly candy. The best treatment was obtained at a concentration of 1.5% cinnamon and 5% red seaweed carrageenan with chemical characteristics water content 11.49%, antioxidant activity 50.26%, pH value 4.82%, physical characteristics colour (brightness) 40.72%, texture hardness 2.3%, adhesiveness 3.1%, elasticity 2.76%, colour preference 4.66%, aroma preference, 4.32%, flavour preference 4.66%, elasticity texture preference 4.56%, taste 4.80%, and overall 4.04%.